An efficient Navier-Stokes solver for automotive aerodynamics - Rannacher, Rolf; Becker, Christian; Turek, Stefan (Mathematics - key technology for the future, 2003)
The aim of this project is the development of efficient and robust numerical methods for the simulation of industrial flows, particularly for incompressible flows in and around vehicles. Since the corresponding flow configurations lead to very huge systems of nonlinear equations with fully nonstationary behavior, the CPU requirements are so high such that special data and matrix structures and hardware-oriented implementation techniques have to be realized. These must be able to exploit a significant percentage of the potentially available computing power of almost 1 GFLOP/s on modern hardware in combination with the powerful FEM discretization and parallel multigrid solution techniques on the mathematical software side. This project is carried out in cooperation with DaimlerChrysler AG at Stuttgart (Dr. M. Wessels, Research and Technology FT1/FB, E222).